Randomised phase II trial of capecitabine plus oxaliplatin with continuous versus intermittent use of oxaliplatin as adjuvant chemotherapy for stage II/III colon cancer (CCOG-1302 study). (February 2021) - Nakayama, Goro; Takano, Nao; Taniguchi, Hiroya; Ishigure, Kiyoshi; Yokoyama, Hiroyuki; Teramoto, Hitoshi; Hashimoto, Ryoji; Sakai, Mitsuru; Ishiyama, Akiharu; Kinoshita, Takashi; Hayashi, Naomi; Nakamura, Masanori; et al.
Abstract: Background: Peripheral sensory neuropathy (PSN) caused by oxaliplatin-based adjuvant chemotherapy adversely affects patients' quality of life. This study evaluated the efficacy and safety of capecitabine plus oxaliplatin (CAPOX) with intermittent oxaliplatin use compared with the standard CAPOX in adjuvant therapy for colon cancer. Patients and methods: Patients with curative resection for stage II/III colon cancer were randomly assigned to receive either CAPOX with continuous oxaliplatin (eight cycles of CAPOX) or CAPOX with intermittent oxaliplatin (two cycles of CAPOX, four cycles of capecitabine and two cycles of CAPOX). The primary end-point was the 1-year PSN rate, and the key secondary end-point was disease-free survival (DFS). Results: Two hundred patients were enrolled in the intent-to-treat population. After 4 patients withdrew, 196 patients were included in the safety analysis. The overall treatment completion rate was 65% for continuous vs. 89% for intermittent treatment ( p  < 0.001). The 1-year PSN rate was 60% (95% confidence interval [CI], 50%–70%) for continuous and 16% (95% CI, 10%–25%) for intermittent treatment ( p  < 0.001). After a median follow-up of 52 months, 40 events (20%) were observed. The 3-year DFS was 81% (95% CI, 71%–87%) for continuous and 84% (95% CI, 75%–90%) for intermittent treatment (hazard ratio [HR], 0.87; 95% CI, 0.47–1.63). Among patients with high-risk disease (T4 or N2-3), the 3-year DFS was 57% for continuous vs. 74% for intermittent treatment (HR, 0.66). Conclusion: CAPOX with planned intermittent oxaliplatin may be feasible as an adjuvant therapy for colon cancer and substantially reduce the duration of long-lasting PSN. Trial identifier: UMIN000012535. Highlights: This study was the first to evaluate adjuvant capecitabine plus oxaliplatin (CAPOX) with intermittent oxaliplatin for colon cancer. Intermittent CAPOX reduced long-lasting peripheral sensory neuropathy compared with standard continuous CAPOX. The efficacy of intermittent CAPOX was consistent with standard continuous CAPOX.